Concomitant hypohyperdontia: Mesiodens and agenesis of a maxillary central incisor in the primary dentition - Santanu Mukhopadhyay; Subrata Saha; Chiranjit Ghosh; Pinaki Roy (Wolters Kluwer Medknow Publications, 2018)
Simultaneous occurrence of supernumerary and agenesis of the teeth is called concomitant hypohyperdontia (CHH). The condition is rare with unknown etiology. CHH may occur in both the jaws and is more common in the permanent and mixed dentition. In this article, we describe a case of nonsyndromic CHH in the primary dentition. A 5-year-old boy showed a conical mesiodens and missing left primary central incisor. Radiographic examination of the patient did not reveal any anomalous succedaneous permanent teeth.